Peran Program Promosi Kesehatan di Tempat Kerja untuk Kesehatan Pekerja: Systematic Literature Review - Abellya Zuleika Jusuf; Evi Martha (Universitas Malahayati Lampung, 2025)
ABSTRACT Workplace health promotion programs are recommended to improve workers' health, productivity, and overall performance. Well-designed and consistently implemented interventions tend to be more successful in achieving health goals. This study employed a systematic literature review approach to determine the role of workplace health promotion programs for workers' health, with five databases from Pubmed, Science Direct, Cochrane Library, Google Scholar, and Wiley Online Library with the keywords